Students’ Moral Crisis in the Digital Era: A Tarbawi Hadith Analysis from the Perspective of Character Education - Erna Marstiyaningtiyas; M Suparta; Romlah Abubakar Askar (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
The development of digital technology has significantly transformed students’ behavior and social interaction patterns. Besides providing easier access to information and learning resources, the digital era has also triggered various moral crises, including declining communication ethics, cyberbullying, reduced respect for teachers, and the misuse of social media. This study aims to analyze the crisis of students’ adab (moral conduct) in the digital era through the perspective of hadith tarbawi and to examine the relevance of prophetic educational values in strengthening character education. This study employed a qualitative approach using library research methods. Data sources were obtained from hadith tarbawi, scientific journal articles, books, and relevant studies published within the last five years. The data were analyzed using content analysis techniques through data reduction, categorization, interpretation, and conclusion drawing. The findings reveal that hadith tarbawi possesses strong relevance to character education in the digital era through values such as honesty, responsibility, respect for teachers, self-control, compassion, discipline, and exemplary behavior. These values serve as moral and spiritual foundations in shaping students with ethical digital behavior, noble character, and the ability to respond wisely to technological advancements. Therefore, the integration of hadith tarbawi into modern education is essential to strengthen holistic and sustainable character education.